A note on interpreting damn expressives: transferring the blame*. (4th September 2014) - FRAZIER, LYN; DILLON, BRIAN; CLIFTON, CHARLES
Abstract : Expressives like damn convey a negative attitude toward an entity or toward a situation. What is particularly interesting about such expressions is the looseness of the relation between their syntax, which is the syntax of normal attribute adjectives, and their interpretation (Potts2005, 2007 ). An experiment on various negative expressives manipulated the placement of the expressive as a prior utterance, or inside the subject or inside an object of the verb or preposition. Experimental participants were asked what the speaker was most likely to have a negative attitude towards − the subject, the object, or the entire situation. The test items were of two types, 'non-causal' and 'causal', exemplified by The holiday is on the damn weekend and The dog is on the damn couch . In the non-causal items, the subject (holiday) cannot plausibly be taken as being responsible for the state of affairs described. However, in the causal items, the subject might be responsible for the state of affairs described. The same range of interpretations was observed for all placements of damn . The prior utterance condition ( Damn. The dog is on the couch .) yielded more entire situation interpretations than the sentence-internal damn items. Overall, subject damn items yielded more subject interpretations than object damn items . However, as predicted by the hypothesis that blame would devolve on a potentially responsible agent (theculprit hypothesis ), there were more subject interpretations in the causal items than in the non-causal items. The results suggest that considerable pragmatic inferencing is involved in the interpretation of expressives, consistent with a proposal that an expressive constitutes a separate speech act.